BRICS Shaping the Course of Humanity - Bricsology (Journal of BRICS Studies)
Opening the 14th summit of the BRICS, the Chinese president, Xi Jinping, said the BRICS had demonstrated resilience and vitality, that they together faced many shared challenges and opportunities. They practically coordinated their efforts, enhanced cooperation and used solidarity to confront shared difficulties. Held under the 2022 theme -Fostering High-quality Partnership and Embarking on a New Journey of BRICS Cooperation- the BRICS theme hoped to “shape the course of humanity”, Jinping reminded his peers.